Toxicocladosporium aquimarinum sp. nov. and Toxicocladosporium qatarense sp. nov., isolated from marine waters of the Arabian Gulf surrounding Qatar. Issue 10 (5th June 2019) - Fotedar, Rashmi; Sandoval-Denis, Marcelo; Kolecka, Anna; Zeyara, Aisha; Al Malki, Ameena; Al Shammari, Hamad; Al Marri, Masoud; Kaul, R.; Boekhout, Teun
Abstract : The Arabian Gulf surrounding Qatar is distinct from other marine ecosystems due to its high salinity (35–75 PSU) and extreme water temperature fluctuations (11–40 °C). Furthermore, in the last decade, Qatar has been witnessing an industrial boom as well as extensive infrastructure construction activities. Marine micro-organisms, including fungi, remain largely unexplored in the Arabian Gulf. During a 3 year study, we investigated the diversity of marine fungi in coastal waters around Qatar. As a result, two new Toxicocladosporium species were isolated from the Qatari marine environment. Molecular and phylogenetic analyses of rRNA gene sequences of five loci, namely the internal transcribed spacer 1 and 2 regions and the D1/D2 domains of the large subunit rRNA, actin, RNA polymerase second largest subunit and beta-tubulin genes, were used to confirm the identity of the novel species for which we propose the names Toxicocladosporium aquimarinum sp. nov. and Toxicocladosporium qatarense sp. nov.